Simultanous determination of lead, zinc and copper in water by the micro high-speed liquid chromatography following the solvent extraction of the metals as diethyldithio carbamic acid chelates in chloroform - 440685 Yamazaki, M.; Ichinoki, B. S.; Igarashi, R.
PSZJBL